ANALYSIS OF COCONUT LEAF DAMAGE LEVEL AS A RESULT OF ATTACKS BY SEXAVA spp. - Betty K. Lahati; M. Saifudin (Jurnal Inovasi Penelitian, 2022)
Sexava is the main pest that often causes coconut production to decline. This pest attacks coconut plants, especially the coconut leaves. Severe attacks caused only the leaves of coconut leaves to remain, therefore this study was carried out to analyze the level of damage to coconut leaves as a result of attacks by Sexava spp. Damage Intensity (IK) 31% which is included in the medium category. The intensity of damage to coconut leaves in Sulamadaha with a total plant population of 156 and the number of coconut plants affected by 98 coconut trees had a damage intensity (IK) of 17% which was included in the medium category. The intensity of damage to coconut leaves in Tobololo with a total plant population of 140 with the number of coconut plants being attacked by 102 coconut trees has a Damage Intensity (IK) of 11% which is included in the mild category. The conclusion is that at the three locations of coconut plantations, the intensity of damage to coconut leaves is different, which is influenced by the agricultural system at each observation location